IMPLEMENTASI KURIKULUM MERDEKA MELALUI PEMBELAJARAN IPAS MATERI SISTEM PERNAPASAN MANUSIA DI KELAS V SDN MANGUNSARI 1 - Sari, Eva Faniya; Eka Andriani, Aldina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Independent Curriculum in Science Learning on the Human Respiratory System Material covers various important aspects, including high-level thinking skills (HOTS), key components such as literacy, 21st-century competencies referred to as the 4Cs (including Critical Thinking, Communication, Collaboration, and Creativity and Innovation), TPACK (Technological Pedagogical Content Knowledge), and the core values reflected in the Pancasila Student Profile. All of these aspects aim to develop students' critical and creative thinking skills. This study aims to describe the implementation of the Independent Curriculum through Science learning on the human respiratory system material, with a focus on aspects that support the implementation of the curriculum. The subjects of the study were teachers and fifth-grade students at SDN Mangunsari 1. The research adopted a qualitative method, using observation, interviews, and documentation as techniques for collecting data. The analysis process involved several stages, including data reduction, organizing the data for display, and drawing conclusions. The findings reveal that the implementation of the Independent Curriculum at SDN Mangunsari 1 remains suboptimal, particularly in the integration of key aspects of the curriculum into the Science learning process on the human respiratory system material. One of the main obstacles is the low ability of teachers in compiling teaching modules. To overcome this, teachers took the initiative to seek references from various online sources and digital media provided by the Ministry of Education, as well as discussing with more experienced fellow teachers.